Weekend Effect in Children With Stroke in the Nationwide Inpatient Sample. Issue 6 (June 2016) - Adil, Malik M.; Vidal, Gabriel; Beslow, Lauren A.
Abstract : Background and Purpose—: Studies have demonstrated differences in clinical outcomes in adult patients with stroke admitted on weekdays versus weekends. The study's objective was to determine whether a weekend impacts clinical outcomes in children with ischemic stroke and hemorrhagic stroke. Methods—: Children aged 1 to 18 years admitted to US hospitals from 2002 to 2011 with a primary discharge diagnosis of ischemic stroke or hemorrhagic stroke were identified by International Classification of Disease, 9th Revision, codes. Logistic regression estimated odds ratios and 95% confidence intervals for in-hospital mortality and discharge to a nursing facility among children admitted on weekends (Saturday and Sunday) versus weekdays (Monday to Friday), adjusting for potential confounders. Results—: Of 8467 children with ischemic stroke, 28% were admitted on a weekend. Although children admitted on weekends did not have a higher in-hospital mortality rate than those admitted on weekdays (4.1% versus 3.3%; P =0.4), children admitted on weekends had a higher rate of discharge to a nursing facility (25.5% versus 18.6%; P =0.003). After adjusting for age, sex, and confounders, the odds of discharge to a nursing facility remained increased among children admitted on weekends (odds ratio, 1.5; 95% confidence interval, 1.1–1.9; P =0.006). Of 10 919 children with hemorrhagic stroke, 25.3% were admitted on a weekend. Children admitted on weekends had a higher rate of in-hospital mortality (12% versus 8%; P =0.006). After adjusting for age, sex, and confounders, the odds of in-hospital mortality remained higher among children admitted on weekends (odds ratio, 1.4; 95% confidence interval, 1.1–1.9; P =0.04). Conclusions—: There seems to be a weekend effect for children with ischemic and hemorrhagic strokes. Quality improvement initiatives should examine this phenomenon prospectively. Abstract : Supplemental Digital Content is available in the text.